Transgenerational sperm DNA methylation epimutation developmental origins following ancestral vinclozolin exposure. Issue 7 (3rd July 2019) - Skinner, Michael K.; Nilsson, Eric; Sadler-Riggleman, Ingrid; Beck, Daniel; Ben Maamar, Millissia; McCarrey, John R.
ABSTRACT: A number of environmental factors from nutrition to toxicants have been shown to promote the epigenetic transgenerational inheritance of disease and phenotypic variation. This requires alterations in the germline (sperm or egg) epigenome. Previously, the agricultural fungicide vinclozolin was found to promote the transgenerational inheritance of sperm differential DNA methylation regions (DMRs) termed epimutations that help mediate this epigenetic inheritance. The current study was designed to investigate the developmental origins of the transgenerational DMRs during gametogenesis. Male control and vinclozolin lineage F3 generation rats were used as a source of embryonic day 13 (E13) primordial germ cells, embryonic day 16 (E16) prospermatogonia, postnatal day 10 (P10) spermatogonia, adult pachytene spermatocytes, round spermatids, caput epididymal spermatozoa, and caudal sperm. The DMRs between the control versus vinclozolin lineage samples were determined for each developmental stage. The top 100 statistically significant DMRs for each stage were compared. The developmental origins of the caudal epididymal sperm DMRs were assessed. The chromosomal locations and genomic features of the different stage DMRs were investigated. In addition, the DMR associated genes were identified. Previous studies have demonstrated alterations in the DMRs of primordial germ cells (PGCs). Interestingly, the majority of the DMRs identified in the current study for the caudal sperm originated during the spermatogenic process in the testis. A cascade of epigenetic alterations initiated in the PGCs appears to be required to alter the epigenetic programming during spermatogenesis to modify the sperm epigenome involved in the transgenerational epigenetic inheritance phenomenon.